2011
DOI: 10.1002/pi.3048
|View full text |Cite
|
Sign up to set email alerts
|

Composites of chitosan with acid‐soluble collagen from jumbo squid (Dosidicus gigas) by‐products

Abstract: Biodegradable films of chitosan with acid‐soluble collagen (ASC) isolated from jumbo squid by‐products were prepared using solution‐mixing and film‐casting techniques. The main goal of the study reported was to evaluate the potential application of ASC as an additive in the preparation of biofilms in composites with commercial chitosan (85% deacetylated, viscosity > 400 MPa s and molecular weight of 570.3 kDa). Thermal properties, scanning electron microscopy (SEM) images, mechanical properties, water vapor ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
2
21
1
2
Order By: Relevance
“…The EB percentage showed a significant decrease for the film with the control gelatin, meaning that the film became less plastic. These results contrast to those reported for the chitosan and collagen films, where the incorporation of collagen increased the elongation percentage, acting as a plasticizer, although there are also reports that show lower EB for edible chitosan‐gelatin films, and results are very similar to chitosan films with carvacrol …”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The EB percentage showed a significant decrease for the film with the control gelatin, meaning that the film became less plastic. These results contrast to those reported for the chitosan and collagen films, where the incorporation of collagen increased the elongation percentage, acting as a plasticizer, although there are also reports that show lower EB for edible chitosan‐gelatin films, and results are very similar to chitosan films with carvacrol …”
Section: Resultscontrasting
confidence: 99%
“…Free water has been related to a decrease of the elastic modulus (CH‐G0) and an increase in the percentage of elongation (CH‐G0), but the results in this study are contrary, which could indicate a low free water content. The elastic modulus range for the films in this study ( ca 1300–1600 MPa) is comparable to that reported for chitosan‐gelatin films . It should be noted that the CH‐G52 film showed the lowest values of TS and MS and the highest EB among the gelatin films treated with ultrasonic pulses; these results are similar to those reported for cuttlefish gelatin‐chitosan films …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the increase in G′ (approximately 50 °C) can be attributed to aggregation of the unfolded protein, which results in the formation of irreversible gels. This aggregation was due to conformational changes associated with hydrophobic interactions as well as disulphide bonds, which contribute to the cross‐linking responsible for the elasticity that dominates the gel structure (Arias‐Moscoso et al ., ). The incorporation of 1–2% chitosan slightly increased G′ between 33 and 50 °C, indicating that chitosan participated in the gel formation.…”
Section: Resultsmentioning
confidence: 72%
“…Aldehyde groups introduced into starch by periodic acid oxidation may condense with amino groups of chitosan, thus giving a novel type of cross‐linked polymer. Ezquerra‐Brauer et al 16 blend collagen from jumbo squid with chitosan and report on barrier, mechanical, and thermal properties of films. This paper is also interesting because the collagen originates from waste of a marine organism that has significant economic importance for the seafood industry in the Baja Californica regions of Mexico.…”
mentioning
confidence: 99%